PENGEMBANGAN MEDIA PEMBELAJARAN PRAKTIK SISTEM KELISTRIKAN MOBIL PADA MATA KULIAH KELISTRIKAN OTOMOTIF DI UNIVERSITAS PGRI YOGYAKARTA - Indrajaya, Ma ruf; Purnomo , Bayu Gilang (Journal of Automotive Technology Vocational Education, 2024)
Research on the development of washer wiper system learning media aims to increase students' understanding in practical learning activities for body electrical systems in the automotive electricity course at the Automotive Technology Vocational Education Program at PGRI Yogyakarta University. This type of research is Research and Development (R&D) using the ADDIE model. This model has 5 development stages, namely: 1) Analysis (analysis) 2) Design (design) 3) Development (development) 4) Implementation (implementation) and 5) Evaluation (evaluation). Feasibility and functional testing of the washer wiper system learning media was carried out in the automotive technology vocational education laboratory by media expert lecturers and material experts. The results of these tests were that the washer wiper system learning media developed could be used as a learning medium in automotive electrical courses. The average score of media expert lecturers is 88% and material expert lecturers is 88%, the washer wiper system learning media is suitable and good to use as a learning medium. The results of the trial with 30 question points that were taken, as many as 91% of students stated that the washer wiper system learning media was suitable and good as a learning media for automotive electrical systems. The results of students' practical tests using the washer wiper system learning media received an average score of 82.86 in the good category so that the washer wiper learning media can improve students' understanding.   Key words: development, learning media, automotive electricity, washer wiper